2015
DOI: 10.1111/ddi.12327
|View full text |Cite
|
Sign up to set email alerts
|

Regional variability in extinction thresholds for forest birds in the north‐eastern United States: an examination of potential drivers using long‐term breeding bird atlas datasets

Abstract: Aim Demand for quantitative conservation targets has yielded a search for generalities in habitat thresholds, particular amounts of habitat at which extinction probabilities change strongly. These thresholds are thought to vary across regions, but investigation of this variability has been limited. We tested whether thresholds (of forest separating extinction from persistence) increased as either average forest cover in landscapes decreased or the degree of fragmentation increased. Location Massachusetts, Mich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Many empirical studies also have found ecological thresholds within the range identified by our study. For example, Desrochers et al () show that > 50% habitat loss or conversion can lead to loss of bird species from regional assemblages in Ontario, Canada and van der Hoek et al () report bird extinction thresholds with 10–93% forest loss or conversion in northeastern United States. Although the identification of a single ‘magic’ (Matthews et al ) threshold value may be attractive from a conservation perspective (Johnson ), threshold values often demonstrate considerable variability even within taxonomic groups and simple landscapes (reviewed by Swift and Hannon ).…”
Section: Discussionmentioning
confidence: 99%
“…Many empirical studies also have found ecological thresholds within the range identified by our study. For example, Desrochers et al () show that > 50% habitat loss or conversion can lead to loss of bird species from regional assemblages in Ontario, Canada and van der Hoek et al () report bird extinction thresholds with 10–93% forest loss or conversion in northeastern United States. Although the identification of a single ‘magic’ (Matthews et al ) threshold value may be attractive from a conservation perspective (Johnson ), threshold values often demonstrate considerable variability even within taxonomic groups and simple landscapes (reviewed by Swift and Hannon ).…”
Section: Discussionmentioning
confidence: 99%
“…Anthropogenic land use and climate change are altering species distributions (Chen, Hill, Ohlemüller, Roy, & Thomas, ; Hickling, Roy, Hill, Fox, & Thomas, ; Parmesan, ; Parmesan & Yohe, ; Sparks, Roy, & Dennis, ; Van der Hoek, Renfrew, & Manne, ; Van der Hoek et al, ; Walther et al, ). Predicting how migratory species might respond to landscape level changes presents additional challenges as breeding and wintering habitats generally occur at geographically disjoint locations (Knudsen et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic land use and climate change are altering species distributions (Chen, Hill, Ohlemüller, Roy, & Thomas, 2011;Hickling, Roy, Hill, Fox, & Thomas, 2006;Parmesan, 2006;Parmesan & Yohe, 2003;Sparks, Roy, & Dennis, 2005;Van der Hoek, Renfrew, & Manne, 2013;Van der Hoek et al, 2015;Walther et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Also, although the percentage of suitable habitat may be the most important and widely used variable, threshold responses may change with different landscape configurations such as the degree of fragmentation. Notably, some of these challenges have already been addressed (Jansson and Angelstam 1999, Villard et al 1999, Suarez-Rubio et al 2013, Van der Hoek et al 2015. We argue that the applicability of the threshold concept, even though the number of studies is increasing, may benefit from more refined analyses that include the matrix (Boesing et al 2018), and consider historical land use changes and other variables such as historical climate stability that help identify the mechanisms behind the responses.…”
mentioning
confidence: 95%
“…Even though there is an increasing array of literature involving thresholds with different taxonomic groups (Fig. 1), some controversies exist regarding their applicability, e.g., not all species in a community have the same responses (Lindenmayer et al 2005, Estavillo et al 2013, and the results of studies may not be transferable across regions, e.g., species may have different threshold responses in different locations (van der Hoek et al 2013). Also, although the percentage of suitable habitat may be the most important and widely used variable, threshold responses may change with different landscape configurations such as the degree of fragmentation.…”
mentioning
confidence: 99%